Membrane Technologies for Lactic Acid Separation from Fermentation Broths Derived from Renewable Resources - Maria Alexandri; Roland Schneider; Joachim Venus (Membranes, 2018)
Lactic acid (LA) was produced on a pilot scale using a defined medium with glucose, acid whey, sugar bread and crust bread. The fermentation broths were then subjected to micro- and nanofiltration. Microfiltration efficiently separated the microbial cells. The highest average permeate flow flux was achieved for the defined medium (263.3 L/m2/h) and the lowest for the crust bread-based medium (103.8 L/m2/h). No LA losses were observed during microfiltration of the acid whey, whilst the highest retention of LA was 21.5% for crust bread. Nanofiltration led to high rejections of residual sugars, proteins and ions (sulphate, magnesium, calcium), with a low retention of LA. Unconverted sugar rejections were 100% and 63% for crust bread and sugar bread media respectively, with corresponding LA losses of 22.4% and 2.5%. The membrane retained more than 50% of the ions and proteins present in all media and more than 60% of phosphorus. The average flux was highly affected by the nature of the medium as well as by the final concentration of LA and sugars. The results of this study indicate that micro- and nanofiltration could be industrially employed as primary separation steps for the biotechnologically produced LA.